Acute calcific tendonitis of dorsal interosseous muscles of the hand: uncommon site of a frequent disease (Reumatismo, 2017)
Acute calcific tendinopathy is one of the manifestations of hydroxyapatite crystal deposition disease. While it is more frequent in the shoulder, it has been described in virtually all areas of the body, but rarely in the muscles of the hand. Its etiopathogenesis is not yet fully understood and despite being a fairly frequent condition, it is commonly misdiagnosed. The onset of the disease is usually acute and resolves spontaneously. Acute calcific tendinitis of the interosseous tendons of the hand is an uncommon site of a frequent condition. The clinical presentation is similar to other entities, thus errors in diagnosis frequently occur, resulting in over-treatment or unnecessary tests. We describe a case of acute calcific tendinitis of the interosseous muscles of the hand with a brief review of the current literature with emphasis on diagnostic imaging methods.